ANALISIS PEMANFAATAN LAHAN PERMUKIMAN di KAWASAN BERLERENG KECAMATAN SINGKIL - Manabung, Patrick I. I.; Tilaar, Sonny; Gosal, Pierre H. (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
Manado City is an area that is very vulnerable to disaster aspects, one of which is landslides, due to the geographical and geological conditions of the region. Manado City has a very varied topography, one of which is in Singkil District. Based on data from the Singkil District Central Statistics Agency in 2019 Figures, there are 6 Kelurahans that have a sloping topography. While looking at the existing one in Singkil District, the sloped land has been used as a residential area. Land use in the city of Manado, especially the Singkil sub-district as a residential area, continues to increase. This can be seen from the construction of residential housing, which tends to have a negative impact on the local community because the construction is not in accordance with the existing spatial plan. The purpose of this study was to identify the distribution of settlements in the sloping area of Singkil district and to analyze the use of residential land in the sloped area of Singkil district. The data collection method in this study used Field Observation, Survey, Documentation and Mapping techniques and for the spatial analysis method consisting of digitization techniques, slope analysis techniques, Overley analysis techniques and descriptive analysis techniques. From the results of the analysis of the distribution of settlements, for the distribution of settlements in Singkil District, the direction of the distribution of settlements tends to be in the highlands. Based on the results of the analysis of land use in Singkil District, for Settlement covering an area of 91.22Ha, Cemetery covering an area of 4.25Ha, Sports Field covering an area of 0.80Ha, Services covering an area of 7.60Ha, Business covering an area of 5.55Ha, Industry covering an area of 0.40Ha, Roads covering an area of 22 ,35Ha, River area of 0.70Ha, and Others covering an area of 22.65Ha.